2021
DOI: 10.7554/elife.72345
|View full text |Cite
|
Sign up to set email alerts
|

Specialized neurons in the right habenula mediate response to aversive olfactory cues

Abstract: Hemispheric specializations are well studied at the functional level but less is known about the underlying neural mechanisms. We identified a small cluster of cholinergic neurons in the dorsal habenula (dHb) of zebrafish, defined by their expression of the lecithin retinol acyltransferase domain containing 2a (lratd2a) gene and their efferent connections with a subregion of the ventral interpeduncular nucleus (vIPN). The lratd2a-expressing neurons in the right dHb are innervated by a subset of mitral cells fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…In this species, asymmetries are restricted to the dorsal habenula (dHb) and consist of different relative proportions between two nuclei, an early-born lateral one (dHbl) and a late-born medial one (dHbm), which prevail respectively on the left and the right side ( Gamse et al, 2005 ; Aizawa et al, 2007 ; deCarvalho et al, 2014 ). Asymmetries in dHb result in differential processing of sensory signals between the left and the right habenula sides ( Dreosti et al, 2014 ) and their abolition affects behavioral and emotional responses to environmental cues, including fear responses, food seeking, and light preference ( Facchin et al, 2015 ; Duboué et al, 2017 ; Zhang et al, 2017 ; Chen et al, 2019 ; Choi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this species, asymmetries are restricted to the dorsal habenula (dHb) and consist of different relative proportions between two nuclei, an early-born lateral one (dHbl) and a late-born medial one (dHbm), which prevail respectively on the left and the right side ( Gamse et al, 2005 ; Aizawa et al, 2007 ; deCarvalho et al, 2014 ). Asymmetries in dHb result in differential processing of sensory signals between the left and the right habenula sides ( Dreosti et al, 2014 ) and their abolition affects behavioral and emotional responses to environmental cues, including fear responses, food seeking, and light preference ( Facchin et al, 2015 ; Duboué et al, 2017 ; Zhang et al, 2017 ; Chen et al, 2019 ; Choi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many previous experimental studies exploiting direct chemical place preference (Braubach et al, 2009; Koide et al, 2009; Hussain et al, 2013; Krishnan et al, 2014; Wakisaka et al, 2017; Lucon-Xiccato et al, 2020; Choi et al, 2021) the tested compound was not marked, inserted locally with a brief shot and was assumed to remain localized while the animal could freely explore the test chamber. Hence there have been large uncertainties over when the animal was actually in contact with the compound and at what concentration, which restricted the behavioral analyses to basic measurements over short runs.…”
Section: Resultsmentioning
confidence: 99%
“…Representative trajectories of a fish in contact with CA are shown in figure 4A: it homogeneously occupies all available space during control or below a concentration threshold, but when CA above the concentration threshold is infused the fish globally avoids this side of the setup, though some short incursions are still performed from time to time. To quantify this behavior we computed the time-based preference index ( PI t ), a quantity that has been widely used in the literature (Koide et al, 2009; Mann et al, 2003; Wakisaka et al, 2017; Lucon-Xiccato et al, 2020; Choi et al, 2021; Herrera et al, 2021) and defined as:…”
Section: Resultsmentioning
confidence: 99%
“…Using in vivo Ca 2+ imaging, several studies have demonstrated that the sensory responses of dHb neurons are asymmetric and subpopulation-specific. The left and right dHb neurons preferentially responded to visual and olfactory cues, respectively ( Jetti et al, 2014 ; Zhang et al, 2017 ; Chen et al, 2019 ; Choi et al, 2021 ). New imaging approaches ( Ahrens et al, 2013 ; Voleti et al, 2019 ; Zhang Z. et al, 2021 ) as well as novel biosensors ( Patriarchi et al, 2018 ; Mohr et al, 2020 ; Sha et al, 2020 ) may facilitate studies on the larger scale neural basis of habenula-related behaviors.…”
Section: Discussionmentioning
confidence: 99%